Dietary Diversity in Adolescents at State Junior High School 4 Depok, Sleman Regency, Yogyakarta: A Descriptive Study - Wulan, Yuni Kartika; Prasetyaningrum, Yunita Indah; Kadaryati, Sri; Wardani, Desy Fitria (EXSACT-A, 2023)
Adolescents require balanced nutrition for their future growth and development. Adolescence is a time when there is a high risk of weight gain, especially in eating habits. A diverse diet for adolescents makes it easier to fulfill their need for various nutrients. This study aims to describe the dietary diversity of adolescents in state junior high school 4 Depok, Sleman Regency, Yogyakarta. This research was quantitative, using an analytic observational approach and a cross-sectional design. A purposive sampling technique was used to select 41 respondents. IDDS (Individual Dietary Diversity Scores) was used to measure dietary diversity based on nine food groups such as starch; green vegetables; vitamin A-rich fruits and vegetables; other fruits and vegetables; organ meats; fish, meat, and other processed meats products; legumes, nuts, and seeds; and dairy products. The majority of the adolescents, i.e. 21 individuals (51.2%), had a medium dietary diversity, while the remaining 20 individuals (48.8%) had a low dietary diversity. The adolescents consumed mainly starch (staple foods), other fruits and vegetables; eggs; fish, meat, and processed products; and dairy products. Adolescents from state junior high school 4 Depok Sleman Yogyakarta were mainly classified as having medium dietary diversity. Keywords: adolescents, dietary diversity, school age